Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd004767.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for cutaneous molluscum contagiosum

Abstract: No single intervention has been shown to be convincingly effective in treating molluscum contagiosum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 49 publications
0
30
0
6
Order By: Relevance
“…The average time for resolution is approximately 6 months but may take years. 12 Treatment is essentially the same as that for HPV; curettage is sometimes used but is often painful and may lead to scarring and so is not generally recommended 6,12 for ED treatment. Extensive or recalcitrant molluscum may occur in the immunosuppressed or immunocompromised patient, and human immunodeficiency virus (HIV) infection should be considered.…”
Section: Cutaneous Wartsmentioning
confidence: 99%
“…The average time for resolution is approximately 6 months but may take years. 12 Treatment is essentially the same as that for HPV; curettage is sometimes used but is often painful and may lead to scarring and so is not generally recommended 6,12 for ED treatment. Extensive or recalcitrant molluscum may occur in the immunosuppressed or immunocompromised patient, and human immunodeficiency virus (HIV) infection should be considered.…”
Section: Cutaneous Wartsmentioning
confidence: 99%
“…7,10 Chemical agents such as silver nitrate, phenol and trichloroacetic acid, in resistant lesions in immunocompromised patients topical antiviral agent cidofovir (5%), intralesional or systemic interferon alpha, imiquimod (5%) cream, salicylic acid, glycolic acid, tretinoin, tazortene, 5% sodium nitrite co-applied daily with 5% salicylic acid topical preparations, podofilox, liquefied phenol, tretinoin, cantharidin, potassium hydroxide, adapelene 1% cream have been reported. 5,7,10 Oral treatment with cimetidine is another option. 7,10 A review of Cochrane database including 495 cases indicated that no therapy was universally and convincingly effective in treatment of MC.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 A review of Cochrane database including 495 cases indicated that no therapy was universally and convincingly effective in treatment of MC. 10 Most of the therapies must be repeated for a couple of times and some of which may be painful for children.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment, if used, is intended to accelerate resolution through destruction of the lesions to induce an inflammatory response 6. Possible reasons to treat molluscum contagiosum include: alleviation of discomfort including itching; for cosmetic reasons; because of social stigma associated with many lesions; limiting spread to other areas of the body or other people; and to prevent scarring, secondary infection, trauma and bleeding of lesions 6…”
Section: About Molluscum Contagiosummentioning
confidence: 99%
“…Cryotherapy may be used in older children or adults, by a healthcare professional experienced in the procedure 2. Curettage is also used but may be painful and can result in scarring; squeezing can also result in scarring, and occasionally in the formation of large abscesses due to disruption of virus into the dermis 6. Treatment with an emollient might help relieve itching, and a mild topical corticosteroid (e.g.…”
Section: About Molluscum Contagiosummentioning
confidence: 99%